2023
DOI: 10.3390/nu15071565
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Salt-Intake on a Natural Gut Ecosystem in Wildling Mice

Abstract: The mammalian holobiont harbors a complex and interdependent mutualistic gut bacterial community. Shifts in the composition of this bacterial consortium are known to be a key element in host health, immunity and disease. Among many others, dietary habits are impactful drivers for a potential disruption of the bacteria–host mutualistic interaction. In this context, we previously demonstrated that a high-salt diet (HSD) leads to a dysbiotic condition of murine gut microbiota, characterized by a decrease or deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Changes in diet have been reported to have effects upon the glycosylation of mucins, independently of hormonal changes 30 . Furthermore, diet-induced changes in the microbiome also have the potential to influence mucin glycosylation 31 , 32 , and these aspects were not controlled for in our experiments. Together, these in vivo experiments suggest mucin sialylation is the most important aspect of the sex dependent differences of mucin glycosylation of laboratory animals, and also that mucin sulphation may be associated with systemic sex hormone signalling in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diet have been reported to have effects upon the glycosylation of mucins, independently of hormonal changes 30 . Furthermore, diet-induced changes in the microbiome also have the potential to influence mucin glycosylation 31 , 32 , and these aspects were not controlled for in our experiments. Together, these in vivo experiments suggest mucin sialylation is the most important aspect of the sex dependent differences of mucin glycosylation of laboratory animals, and also that mucin sulphation may be associated with systemic sex hormone signalling in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in diet have been reported to have effects upon the glycosylation of mucins, independently of hormonal changes [28]. Furthermore, diet-induced changes in the microbiome also have the potential to in uence mucin glycosylation [29], [30], and these aspects were not controlled for in our experiments. Together, these in vivo experiments suggest mucin sialylation is the most important aspect of the sex dependent differences of mucin glycosylation of laboratory animals, and also that mucin sulphation may be associated with systemic sex hormone signalling in male and female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kumar et al [35] reported a reduction in the abundance of both Firmicutes and Bacteroidetes in the gut of high-salt-fed rats compared to low-salt guts. In another animal study, loss of Lactobacillus and other beneficial genera in Firmicutes was not observed in the high-salt cohort of wilding mice [36], though it was observed in conventional laboratory mice. In a related study on risk factors of hypertension, HSD led to the reduction in beneficial Bacteroides (not B. fragilis) [37].…”
Section: Introductionmentioning
confidence: 92%